164 Effect of cardiac contractility modulation therapy on myocardial work in patients with heart failure with reduced ejection fraction. (8th December 2021) - Masarone, Daniele; Vivo, Stefano De; Errigo, Vittoria; Onofrio, Antonio D'; D'Alterio, Giuliano; Ammedola, Ernesto; Nigro, Gerardo; Pacileo, Giuseppe
Abstract: Aims: Cardiac contractility modulation therapy (CCMT) has been shown to reduce hospitalizations and to improve quality of life in heart failure patients with reduced ejection fraction (HFrEF) who remain symptomatic despite disease-modifying therapies. Strain imaging derived myocardial work (MW) is an emerging tool for evaluating left ventricular mechanics by incorporating systolic deformation and afterload burden in the analysis. To evaluate prospectively the impact of CCMT in HFrEF patients on MW derived parameters in relation to standard echocardiographic indices. Methods and results: We recruited 12 HFrEF patients with indications to CCMT according to current clinical practice. A comprehensive echo-Doppler evaluation, including speckle tracking derived assessment of global longitudinal strain (GLS), was performed before and after three months from the CCM device implantation. Parameters of MW such as global work index (GWI), global constructive work (GCW) global wasted work (GWW), and global work efficiency (GWE) were calculated according to standardized procedures. Median values (interquartile range) were compared for all those parameters from baseline and 3-month follow-up with Wilcoxon Rank Sum test for continuous variables. At three months from CCM implant an improvement of LVEF [from 32% (27–34) to 36% (29–39), P  < 0.05], GLS [from 7.4% (6.2–11.2) to 9.9% (7.5–9.4), P  < 0.05], GWI [from 461 mmHg (372–613) to 589 mmHg (413–696), P  < 0.05], GCW [from 800 mmHg (620–930) to 970 mmHg (644–1009), P  = 0.236], and GWE [from 73% (65–78) to 85% (78–87), P  < 0.05] was observed, with a consistent reduction of GWW [from 161 mmHg (148–227) to 125 mmHg (101–188), P  < 0.05]. We also found a positive correlation between the magnitude of LVEF improvement and the baseline values of GCW ( r  = 0.727, P  = 0.011). Conclusions: At 3 months, CCMT significantly improves standard and advanced left ventricular systolic function indices. This improvement is due to the increase of constructive work and a reduction of wasted work. In addition, the increase of left ventricular ejection fraction can be predicted by the global constructive work levels at baseline.